2021
DOI: 10.1016/j.jsams.2020.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Influence of maturational status in the exercise-induced release of cardiac troponin T in healthy young swimmers

Abstract: Influence of maturational status in the exercise-induced release of cardiac troponin T in healthy young swimmers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 36 publications
0
20
1
Order By: Relevance
“…This is contrary to our expectations, since previous authors suggested that the less mature myocardium in the younger might be more susceptible to exercise-induced elevations of cTn [8,9]. Interestingly though, a recent study reported higher exercise-induced elevations of cTnT in late puberty, suggesting that this might be explained by the higher relative intensities during exercise achieved in this group [13]. In line with this study, our adolescents group also achieved higher cardiac intensities during the test.…”
Section: Discussioncontrasting
confidence: 88%
See 2 more Smart Citations
“…This is contrary to our expectations, since previous authors suggested that the less mature myocardium in the younger might be more susceptible to exercise-induced elevations of cTn [8,9]. Interestingly though, a recent study reported higher exercise-induced elevations of cTnT in late puberty, suggesting that this might be explained by the higher relative intensities during exercise achieved in this group [13]. In line with this study, our adolescents group also achieved higher cardiac intensities during the test.…”
Section: Discussioncontrasting
confidence: 88%
“…Almost one-half of the participants in this study (44%) exceeded the upper reference limit for cTnT in the third blood extraction. Previous studies involving similar assessments and exercise exposures also found high rates of positive detection in both young and adult trained participants [4,[6][7][8]13]. This is particularly relevant for the triage of athletes who develop chest pain that mimics cardiac injury after exercise, and who might have serum cTn drawn in the EDs.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Although no prior study has investigated the effect of puberty on Troponin levels, studies by Cirer-Sastre et al and Legaz-Arrese et al have assessed the effect of exercise-induced release of cardiac markers at different stages of puberty [ 34 , 35 ]. We could demonstrate that hsTnT levels in boys rise from pubertal stage 2 onward and that in all pubertal stages, girls have consistently lower levels than boys, with an increasing effect during puberty.…”
Section: Discussionmentioning
confidence: 99%
“…In order to understand the underlying mechanisms and related clinical implications, several studies have identified potential moderators of exercise-induced cTn elevation. Overall, hs-cTn concentrations was impacted: by exercise duration (Kleiven et al, 2019), intensity (Richardson et al, 2018;Martínez-Navarro et al, 2020) and workload (Cirer-Sastre et al, 2019); maturational status (Martínez-Navarro et al, 2020;Cirer-Sastre et al, 2021); training experience (Tian et al, 2012); gender (Kong et al, 2017;Legaz-Arrese et al, 2017); basal level of cTn (Legaz-Arrese et al, 2015a,c); as well as environment (Li et al, 2016). The possibility of interaction of the moderators needs further investigation.…”
Section: Introductionmentioning
confidence: 99%